Ichtyofauna in the Sok-sok Holbung, Aek Isa small river, Simarpinggan Village, Sipoholon District, North Tapanuli Regency, North Sumatera Province. - Nababan, Bertrand R; Efizon, Deni; ', Windarti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Sok-sok Holbung is a small shallow river in the Dolok Imun plateau with a very good quality of water. A research aims to understand the species, diversity and domination indices of fish in that river had been done from September-October 2016. There were 3 stations, in the upstream, in the middle and in the downstream area of the river. The fish was sampled using scoop net and then they were identified based on Saanin (1968), Kottelat (1993) and Fowler (1940). Samplings were done 2-3 times in each station. Results shown that there were 3 ordos, 4 families, 5 genuses and 5 species fish present in the study area, they were Mystaccoleus padangensis, Tor soro, Homaloptera ripleyi, Channa striata, Clarias batrachus. The diversity index ranged from 0.443- 0.765, while the dominant index was 0.388-0.757. The most common species was H. ripleyi that was present in each sampling site.Keyword: Sok-sok holbung River, Ichtyofauna, Homaloptera ripleyi, Tor soro